Synergistic Temperature Effect on the Acid Corrosion Inhibition of API 5L Grade B Steel Using Eichhornia crassipes Leaf Extract - Laksita Aji Safitri; Eddy Widiyono; Hari Subiyanto; Dimitra Meidina Kusnadi; Yusuf Tanto Kuswanto; Nur Husodo (Institut Teknologi Sepuluh Nopember, 2025)
Corrosion is the deterioration of material properties, particularly metals, due to chemical reactions with the surrounding environment. One of the effective methods to mitigate corrosion is the addition of inhibitors. Organic inhibitors are considered environmentally friendly, cost-effective, and renewable. In this study, an extract of water hyacinth leaves (Eichhornia crassipes) was used as an organic inhibitor. The material tested was API 5L Grade B steel in 1 M HCl solution as the corrosive medium, with testing temperatures of 30 °C, 40 °C, 50 °C, and 60 °C, and inhibitor concentrations ranging from 500 mg to 2500 mg. The corrosion behavior was evaluated using Potentiodynamic Polarization (PDP), Electrochemical Impedance Spectroscopy (EIS), and Weight Loss (WL) methods. The results showed a significant reduction in the corrosion rate of API 5L Grade B steel in 1 M HCl solution when the water hyacinth extract inhibitor was added. In the PDP test, the corrosion rate for the sample without inhibitor reached 107.4 mm/year, while the lowest inhibition efficiency was 1.25% and the highest inhibition efficiency was 97.85%, observed at 50 °C with an inhibitor concentration of 2500 mg. This represents the maximum efficiency among all tested concentrations and temperatures.